2001
DOI: 10.1007/pl00002050
|View full text |Cite
|
Sign up to set email alerts
|

Lebensqualität und psychosoziale Faktoren unter antihypertensiver Therapie Ein Vergleich von Captopril und Quinapril bei geriatrischen Patienten

Abstract: A favorable antidepressive effect of Quinapril in elderly hypertensive patients is concluded and should be studied in further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In these studies, depression, and certain demographic- and disease-related characteristics (e.g., older age, female gender, HTN medication, comorbidity) were associated with poor HRQOL (Heyworth, Hazell, Linehan, & Frank, 2009; Holt et al, 2010; Michalsen et al, 2001; Rueda & Pérez-García, 2006; Ucan & Ovayolu, 2010). In particular, depression has been a consistent risk factor for poor HRQOL in patients with HTN (Heyworth et al, 2009; Holt et al, 2010; Michalsen et al, 2001; Rueda & Pérez-García, 2006; Ucan & Ovayolu, 2010). Few studies indicate that social support may play a protective role in promoting HRQOL in the presence of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, depression, and certain demographic- and disease-related characteristics (e.g., older age, female gender, HTN medication, comorbidity) were associated with poor HRQOL (Heyworth, Hazell, Linehan, & Frank, 2009; Holt et al, 2010; Michalsen et al, 2001; Rueda & Pérez-García, 2006; Ucan & Ovayolu, 2010). In particular, depression has been a consistent risk factor for poor HRQOL in patients with HTN (Heyworth et al, 2009; Holt et al, 2010; Michalsen et al, 2001; Rueda & Pérez-García, 2006; Ucan & Ovayolu, 2010). Few studies indicate that social support may play a protective role in promoting HRQOL in the presence of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Huang et al (2010) presented that higher social support was significantly less likely to improve depression than those without social support among chronic heart disease patients. One study suggested social support as a possible modifiable risk factor for HRQOL among elderly with HTN (Michalsen et al, 2001). While these studies offer some insights as to potential contributors to HRQOL among elderly, to the best of our knowledge, no previous study looked specifically at potential contributors to HRQOL among Asian immigrant elders with HTN.…”
Section: Introductionmentioning
confidence: 99%